(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine the Performance of Employees in Guiding Prisoners at Class IIB prison at Jeneponto Regency. This study used qualitative research. Data collection techniques used observation, interviews with 6 informants. Data analysis used an interactive analysis model. The results showed that the performance of employees in guiding prisoners was quite good but needed to be improved to be more optimal, this was seen from the aspect of quality, performance in guiding prisoners was still lacking even though in providing services and work in accordance with procedures and rules, but there were still a few prisoners get different treatment, quantity, ability of employees were quite good because the selection process was very strict by the state, punctuality and discipline were mandatory duties of employees and arranged time to be more organized and did not other activities that could be hinder employee performance so that activities could run well in accordance with the timeliness, the effectiveness of employees’ performance was good, both in terms of work reports and task completion were run well because they worked in accordance with guidelines and directives, and work performance commitment had completed the task on time and accurately .